Forecasting Kapasitas Tempat Tidur di Rumah Sakit Islam Jakarta Pondok Kopi - Sinlae, Andrey Reynaldi Devada; Hosizah, Hosizah; Nurmalasari, Mieke (Politeknik Negeri Jember, 2026)
In 2022–2023, bed utilization at RSIJ Pondok Kopi was inefficient according to the Barber–Johnson (GBJ) standard, with Bed Occupancy Rates (BOR) of 53% in 2022 and 74% in 2023, both below the ideal range. This inefficiency was partly due to the absence of bed capacity adjustments based on accurate forecasting. This study aimed to conduct bed capacity forecasting at RSIJ Pondok Kopi. This applied retrospective study employed data mining techniques using Tableau with the Exponential Smoothing algorithm. Data on inpatient days and discharged patients from 1992 to 2023 were collected and processed following the Knowledge Discovery in Databases (KDD) framework. One optimal forecasting model was selected for each variable. Bed capacity projections were calculated using BOR assumptions of 75% and 85%, and Turnover Interval (TOI) assumptions of 1 and 3 days, with the Barber–Johnson chart used for evaluation. Forecasted bed requirements were estimated at 183–192 units (2024), 185–194 (2025), 187–196 (2026), 189–197 (2027), and 190–199 (2028). Compared with actual data through May 2024, the hospital had 10 excess beds. Therefore, more intensive promotional strategies are recommended to improve bed utilization.